CATHERINE OF BEDIA: A FEMALE TO THE CRIMINAL JUSTICE. THE INDIVIDUAL AND HIS COMMUNITY IN A CANTABRIC VILLAGE IN THE LATE FIFTEENTH CENTURY (BILBAO). - Muñoz Saavedra, Eduardo (Revista de Historia Social y de las Mentalidades, 2024)
This article aims to analyze, from different perspectives, the presence of a woman in the Spanish royal criminal documentation in the late fifteenth century. Thus, it serves and reflects around various elements that explain the relationship between Catherine of Bedia, a woman from Bilbao village identified as a criminal, and the different spaces and levels of socialization in which she is inserted. In this way, in the first place, historical forces that converge to the existence of royal criminal documents are analyzed; on the other hand, the criminal actions of Catherina are reconstructed, considering her movement, the sense of space, the criminal association and the actions of the court. All that with the purpose of reach, not just the scope of female crime, but the everyday of villain life and their dynamics, structures, and local and global points of inflection.